Analysis of SUMO1-conjugation at synapses - Daniel JA; Cooper BH; Palvimo JJ; Zhang FP; Brose N; Tirard M (ELIFE SCIENCES PUBLICATIONS LTD, 2025)
SUMO1-conjugation of proteins at neuronal synapses is considered to be a major post-translational regulatory process in nerve cell and synapse function, but the published evidence for SUMO1-conjugation at synapses is contradictory. We employed multiple genetic mouse models for stringently controlled biochemical and immunostaining analyses of synaptic SUMO1-conjugation. By using a knock-in reporter mouse line expressing tagged SUMO1, we could not detect SUMO1-conjugation of seven previously proposed synaptic SUMO1-targets in the brain. Further, immunostaining of cultured neurons from wild-type and SUMO1 knock-out mice showed that anti-SUMO1 immunolabelling at synapses is non-specific. Our findings indicate that SUMO1-conjugation of synaptic proteins does not occur or is extremely rare and hence not detectable using current methodology. Based on our data, we discuss a set of experimental strategies and minimal consensus criteria for the validation of SUMOylation that can be applied to any SUMOylation substrate and SUMO isoform.